2021
DOI: 10.20452/pamw.16100
|View full text |Cite
|
Sign up to set email alerts
|

Optimal medical therapy in patients with stable coronary artery disease in Poland. The ISCHEMIA Trial experience

Abstract: Optimal medical therapy (OMT) has been the cornerstone of treatment in patients with stable coronary artery disease, however its proper application remains challenging. Herein, a snapshot of OMT patterns is presented in the ISCHEMIA Trial participants in Poland in comparison to other countries worldwide at the time of their randomization into the trial and at last follow-up visit. It demonstrates the achievable level of OMT goal attainment with the use of contemporary treatment methods and multifaceted, team e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In a certain group of patients, e.g., following cardiac transplantation, with hypertrophic cardiomyopathy or ST-elevation myocardial infarction, the severity of CMD constitutes a potent independent risk factor for clinical deterioration and death. [12] Remodeling of coronary microcirculation vessels leads to decreased density of arterioles and arteriole wall hypertrophy, which further results in increased flow resistance and, thusreduced perfusion. It has been shown that the density of capillaries is inversely correlated with clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In a certain group of patients, e.g., following cardiac transplantation, with hypertrophic cardiomyopathy or ST-elevation myocardial infarction, the severity of CMD constitutes a potent independent risk factor for clinical deterioration and death. [12] Remodeling of coronary microcirculation vessels leads to decreased density of arterioles and arteriole wall hypertrophy, which further results in increased flow resistance and, thusreduced perfusion. It has been shown that the density of capillaries is inversely correlated with clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years a large body of evidence has shown that the control of CV risk factors either in the general population and in patients at high risk, such as those with coronary artery disease (CAD), is very low and that bad adherence to cardioprotective treatment may be one of the most important factors in preventing adequate CV risk factor control in the general population and in patients with CAD. [10][11][12][13][14][15][16] The EUROASPIRE surveys in hospitalized patients with CAD in 24 European countries have consistently shown that the guidelines recommended targets for blood pressure, LDL-cholesterol are critically low. 10 This is related with the insufficient implementation of the optical medical treatment in these patients, particularly the suboptimal use of high-intensity statin therapy, and combination of antihypertensive drugs to achieve recommended targets.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the ISCHEMIA study in Poland clearly shows that this challenge may be overcome by the use of contemporary treatment methods and multifaceted team efforts. 11 In addition, several studies have shown that complex treatment strategies, particularly those using a big number of daily pills, adversely affect adherence, which is substantially improved by treatment simplification. [17][18][19][20][21] Because treatment simplification is probably the most important characteristic of a polypill regimen, this strategy appears to be as the most adequate to improve the reported low efficacy of primary and secondary CV prevention at the population level.…”
Section: Introductionmentioning
confidence: 99%